An Introduction to Inequalities - Beckenbach, Edwin; Bellman, Richard (Anneli Lax new mathematical library., 2012)
Most people, when they think of mathematics, think first of numbers and equations-the number (x)=that number (y). But professional mathematicians, in dealing with quantities that can be ordered according to their size, often are more interested in unequal magnitudes that are equal. This book provides an introduction to the fascinating world of inequalities beginning with a systematic discussion of the relation 'greater than' and the meaning of 'absolute values' of numbers, and ending with descriptions of some unusual geometries. In the course of the book, the reader will encounter some of the more famous inequalities in mathematics. Starting with the basic order properties of real numbers, this book carries the reader through the classical inequalities of Cauchy, Minkowsky and Hörder with many variants and applications. The concluding chapter points the way to other metrics in the plane and the interrelations between geometry (convexity) and algebra (inequalities).